Implementing Educational Technology in Higher Education: A Strategic Approach - Cynthia C. Roberts (Journal of Educators Online, 2008)
Although the move toward implementing technology in higher education is driven by an increasing number of competitors as well as student demand, there is still considerable resistance to embracing it. Adoption of technology requires more that merely installing a product. This paper outlines a framework for a strategic change process that can be utilized by educators for the purpose of the selection as well as successful implementation of educational technologies within their setting, in particular, online course management systems. The four steps of this process include strategic analysis, strategy making, strategic plan design, and strategic plan implementation. The choice to embrace a new system and the extent and speed of its implementation depends upon internal factors such as resources, organizational culture, faculty readiness, anticipated degree of resistance, and the degree of variance from the status quo. A case from the author’s experience provides one example of how the use of distance learning technology was strategically implemented.